Migration routes, stopover sites and home range sizes of Taiga Bean Geese (Anser fabalis fabalis) breeding in northern Sweden and central Norway tracked by GPS tags - Boer, Jorina (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2019)
The Taiga Bean Goose (Anser fabalis fabalis) has shown a recent decrease in population size. For geese breeding in central Scandinavia, the delineation between different subpopu-lations is not entirely clear and more detailed knowledge regarding migratory routes is still lacking. Moulting Taiga Bean Geese caught at Vilhelmina, Sweden were equipped with solar-powered GPS satellite transmitters. In this study the route, timing and stopover use was de-termined for autumn and spring migration. For several major sites the home range was also determined as well as the similarity in space use within and between years for every goose. A total of 13 tagged Taiga Bean Geese eventually provided (partial) telemetry data for three years. Two distinct routes were revealed. The majority flew to Töreboda to stage during spring, before flying to their breeding grounds in southern Västerbotten County, Sweden. Two geese however migrated along the Swedish-Norwegian border to breed in Børgefjell national park, Norway. During autumn all birds departing from northern Sweden used a long duration stop-over at Töreboda before returning to their wintering grounds in Thisted, Denmark. Their autumn migration varied from 11 to 150 days. In contrast, the two Norwegian breeding birds flew straight to their destination in Thisted, generally completing their autumn journey within less than a day. Both groups displayed high fidelity and return rates to their wintering and major stopover sites. Although the data of this study only includes two birds breeding in Norway, the consistently distinct migratory route and behaviour, combined with recent genetic data, indicates that these birds are largely distinct from their Swedish counterparts. Uncovering discrete migratory routes is thus crucial for implementing more targeted conser-vation efforts towards more vulnerable subpopulations. Encompassing 3 years of telemetry data, this study contributes towards a first step in better understanding the delineation and connectivity of flyways of Taiga Bean Geese breeding in Scandinavia.